Robust topological nodal lines in halide carbides. Issue 36 (6th September 2019) - Pham, Anh; Klose, Frank; Li, Sean
Abstract : This study predicts the existence of a symmetry protected nodal line state in Y2 C2 I2 in both 2D and 3D. Abstract : A topological nodal line semimetal is a novel state of matter in which the gapless bulk state extends along the Brillouin zone forming a closed 1D Fermi surface. Here, we theoretically predict that the layered halide carbide Y2 C2 I2 is a novel metal containing interconnected nodal lines protected by the parallel mirror planes k z = 0 and k z = 0.5, characterized by independent mirror Chern numbers (MCNs) | μ 1 | = | μ | = 1. Because of the interlocking 2D nodal lines stacked along the c -axis direction, the topological property is robust both in the 3D bulk as a topological chain metal and in the 2D nanostructure as a topological nodal line. Consequently, Y2 C2 I2 and other related layered halide carbide materials are unique candidates to realize functional topological devices due their size-independent topological properties.